Reply to Comments: Using the Cardio-Ankle Vascular Index (CAVI) or the Mathematical Correction Form (CAVI0) in Clinical Practice - Bart Spronck (International Journal of Molecular Sciences, 2020)
We read with great interest Alizargar et al [...]